'Most Important Events' and Therapeutic Factors: An Evaluation of Inpatient Groups for People with Severe and Enduring Mental Health Difficulties. (December 2016) - Bledin, Kenneth; Loat, Maddy; Caffrey, Anna; Evans, Kathy Bonshor; Taylor, Bethany; Nitsun, Morris
People with severe and enduring mental health difficulties attending groups on 10 inpatient wards were asked to identify the 'Most Important Event' (MIE) in each group session they attended, as part of a routine service evaluation. Using the methods of thematic analysis, five main themes were identified from the 192 Most Important Events recorded over the course of one year: Being part of a group, Communication, Help and support, Hope for the future, and Relationships. The main themes and subthemes were largely compatible with Yalom's therapeutic factors, but also suggested that more fundamental levels of therapeutic factors may be present in groups with people with severe and enduring mental health difficulties. These factors include feeling connected, communication, and a sense of belonging. This evaluation of Most Important Events in inpatient groups adds to the evidence base in the field of group analysis and group psychotherapy.